2020
DOI: 10.1007/s13555-020-00443-2
|View full text |Cite
|
Sign up to set email alerts
|

Night Cream Containing Melatonin, Carnosine and Helichrysum italicum Extract Helps Reduce Skin Reactivity and Signs of Photodamage: Ex Vivo and Clinical Studies

Abstract: Introduction: Extrinsic factors, such as solar radiation and urban pollution, cause damage that alters the structure, function and appearance of skin. The aim of this study was to determine the ability of a night cream containing melatonin, carnosine and Helichrysum italicum extract (referred to here as Night Cream) to reduce extrinsic skin damage, and to evaluate the efficacy of this Night Cream to reduce clinical signs of age and photodamage under normal conditions of use. Methods: Recovery from extrinsic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
(31 reference statements)
0
19
0
2
Order By: Relevance
“…The clinical experiments performed by Santini [ 49 ], Benigni [ 50 ], Vannini [ 51 ] and Campanini [ 52 ] are described in Italian literature and summarized in the article by Appendino et al [ 53 ]. These observations are presented in Table 2 along with additional studies by Facino et al [ 16 ], Voinchet and Giraud-Robert [ 54 ], and a very recent one by Granger et al [ 55 ]. These studies mainly cover treatments of respiratory and dermal conditions.…”
Section: Human Clinical Observationsmentioning
confidence: 74%
“…The clinical experiments performed by Santini [ 49 ], Benigni [ 50 ], Vannini [ 51 ] and Campanini [ 52 ] are described in Italian literature and summarized in the article by Appendino et al [ 53 ]. These observations are presented in Table 2 along with additional studies by Facino et al [ 16 ], Voinchet and Giraud-Robert [ 54 ], and a very recent one by Granger et al [ 55 ]. These studies mainly cover treatments of respiratory and dermal conditions.…”
Section: Human Clinical Observationsmentioning
confidence: 74%
“…The use of creams containing melatonin, carnosine, and Helichrysum italicum extract on skin explants exposed to a mixture of polycyclic aromatic hydrocarbons and heavy metals leads to a reduction in skin damage and irritation [276]. The study demonstrated a significant decrease in pollution-activated transcription factor aryl hydrocarbon receptors (AhR) and type I collagen in melatonin-treated explants.…”
Section: Role Of Melatonin and Its Metabolites In The Attenuation Of ...mentioning
confidence: 97%
“…Its photoprotective, 59,60 antiphotoaging, 10,50,177,245–247 antioxidative damage‐protective, 5,28,86,89,92,189,190 and DNA damage‐repair 28 properties also raise the possibility that melatonin may be useful to slow intrinsic and extrinsic skin aging and may exert melanocyte‐protective properties in vitiligo and perhaps even aging‐associated hair graying resulting from oxidative damage to the HFPU 68 . In fact, melatonin and its metabolites (e.g., AFMK) protect melanocytes in vitro 28 from UV‐induced DNA damage and apoptosis 50,248 when applied both before 249 and immediately after UVB exposure 28 .…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%